The Effect of Implementing an Empathetic Approach on Job Satisfaction Administrative staff at the Faculty of Tarbiyah and Teacher Training Antasari State Islamic University Banjarmasin - Ahmad Salabi; Mufida Istati (CV. Samuel Manurung and Co, 2024)
Job satisfaction of administrative staff is an important factor in the running of the administrative activity process in a higher education environment. . The population in this study were all administrative staff at the Tarbiyah and teacher training faculties of State Islamic University antasari Banjarmasin. The research sample was taken with total sampling. Data collection was carried out using survey techniques in the self-administered survey category, the data analysis technique used in the study was multiple regression analysis. The results showed that there was an influence of the empathy approach in the aspects of providing recognition and appreciation, giving attention to trust and responsibility, career and professional development, and supervision implementation techniques. An empathetic approach to the aspect of fostering conducive personal relationships, especially social and political awareness, has no effect on staff job satisfaction. From the results of the multiple regression analysis, it was found that there was an influence of an empathetic approach in providing recognition and appreciation, paying attention to trust and responsibility, career and professional development, fostering personal relationships that were conducive to staff job satisfaction. Trust and responsibility have a significant influence on job satisfaction